Anamorphic fungi associated with plant litter of the jungle of the State Park "Agua Blanca", Macuspana, Tabasco, Mexico - Martínez-Rivera, Karen; Heredia, Gabriela; Rosique-Gil, Edmundo (Instituto de Ecología, A.C., 2014)
Fungal diversity of protected areas in the state of Tabasco has been poorly studied. Most microscopic saprophytic species are not yet known. This contribution aims to increase our knowledge of the litter-inhabiting anamorphic fungi from the rain forest of the “Agua Blanca” state park. An account of 40 taxa is included, 15 of them had not been reported from Mexico before, and 25 are new records for the Tabasco state. For all the new national records, morphologic description, illustrations, geographical distribution and observations on their taxonomic characters are included.